Internet engagement of Ukrainian teenagers as perceived by their parents - Svyrydenko A. O.; Zubariev O. S. (Український соціум)
The article examines the phenomenon of adolescents’ engagement with the Internet through the prism of parental perception. It analyzes how the digitalization of contemporary society influences adolescents, their interests, needs, and family social relations. The role of Internet is identified as both a space for socialization and a means of self-expression for adolescents, while also highlighting potential risks associated with excessive engagement, including internet addiction and exposure to harmful content. Based on the analysis of in-depth interviews, five primary types of parental attitudes toward adolescents’ engagement with the Internet were identified: “Internet use is the child’s own business”, “Internet use is beneficial for intellectual development”, “Internet use represents a lost childhood”, “Internet use is the price for staying connected”, and “Internet use is a reward for good behavior”. Special attention is given to the issue of parental control, particularly the phenomenon of “parental stalking” – monitoring children’s activity on social media as a means of ensuring their safety. The study distinguishes several strategies parents employ to manage adolescents’ excessive involvement in the digital environment: “Total phone content checks”, “Monitoring children’s social media”, “Complete absence of control”, “Checking specific apps”, “Setting time limits for Internet use” and “Phone confiscation”. The analysis of the transcripts of in-depth interviews demonstrated that although most parents recognize potential risks, effective strategies for regulating children’s digital lives are often lacking. Parental strategies range from strict control to no control at all over adolescents’ online activity. It is noteworthy that none of the parents mentioned the importance of increasing adolescents’ digital literacy. The findings can be used to create recommendations for building effective communication between generations in the context of the digitalization of society. The results obtained open up prospects for further research of the role of parental position in shaping the behavior of Ukrainian adolescents on the Internet, as well as the impact of various models of parental control on their emotional and social well-being.